In-situ Conservation Strategy to Safeguard Sentul Chickens in the Future - Asmara, I.Y.; Anang, A.; Widjastuti, T.; Sujana, E. (KnE Life Sciences, 2017)
Animal genetic resources such as indigenous chickens are part of biodiversity. Sentul chickens are one of indigenous chickens in Indonesia which are regarded as local to Ciamis District in West Java. It is reported that the population of pure Sentul Chickens are in decline. This study was aimed to find out the current population of pure Sentul chickens in three areas in West Java and to develop a conservation strategy to safeguard Sentul chickens in the future. The study used qualitative method to gather data including literature review and key informant interviews. The informants consisted of a leader of farmer group and managers of breeding centers. The interviews were carried out in Ciamis, Majelengka and Bogor Districts. The data were analyzed by descriptive analysis. The results indicated that population of Sentul chickens in Ciamis are in decline, while population in areas outside Ciamis such as Bogor tend to increase. There is a need to develop an in-situ conservation program in which Ciamis District should be assigned to be the center area to provide pure Sentul chickens in West Java. To support the conservation program, stakeholders such as local government, research institutions, universities and farmer groups play important roles. Keywords: in-situconservation strategy, Sentul chickens, animal genetic resources, biodiversity.